Distribution of Mode I Stress Intensity Factors for Single Circumferential Semi-Elliptical Crack in Thick Cylinder - Mohammed, Omar; Ismail, Al Emran; Kareem, AK; Jamian, Saifulnizan; Nemah, MN (International Journal of Integrated Engineering, 2019)
In this paper, mode I stress intensity factors (SIFs) are calculated numerically by finite element software ANSYS, for a single semi-elliptical circumferential crack on a thick cylinder. The examined cracks were located either on the external or internal surface of the cylinder and subjected to two different types of loadings, tension and internal pressure, applied separately. To present results in a more comprehensive form, dimensionless analysis is used, and a wide variation limit of parameters that define the crack geometry is considered. The ratio of crack depth to crack length ranging between 0.4 to 1.2, the ratio of crack depth to cylinder wall thickness vary between 0.2, 0.5 and 0.8, and the ratio of the cylinder wall thickness to the cylinder internal radius 0.25. Based on the obtained results, distributions of SIFs found to be symmetric along the crack front. The location where the maximum SIFs on the crack front attained is strongly affected by the change of aspect ratio, and external cracks generally exhibit a higher SIFs than those of internal cracks. It is also found a significant effect for the relative depth of the crack on SIFs value, which could accelerate the fracture process.